Evaluation of Bone Mineral Density Determinants in Patients with Spinal Cord Injury: a Systematic Review - Joanna Cieplińska; Agnė Predkelienė; Izabela Rutkowska; Anna Kopiczko (Rehabilitacja Medyczna)
Purpose of Review: Studies describing the bone mineral density (BMD) loss rate in people after spinal cord injury (SCI) haveyielded inconclusive results. This systematic review is aimed at assessing the prevalence of low BMD in SCI patients and summarisingrecent data on the impact of various factors on BMD levels in different parts of the skeleton. This review was modelledon the basis of the PRISMA statement. A systematic literature search in ScienceDirect, PubMed and EBSCO was conducted.The search criteria included bone mineral density, spinal cord injury, young adults, and adults. The studies were conductedon 705 women and men following SCI. Individuals with SCI exhibited a higher prevalence of low BMD compared to thecontrols. The impact of injury parameters on BMD varied across different skeletal locations.Recent fifi ndings: The results revealed various correlations between BMD and age, sex, somatic variables, diet as well as biochemical parameters. However, no significant relationships were found between BMD and serum 25(OH)D, calcium, vitamin D or protein intakes. BMD was negatively correlated with parathyroid hormone (PTH) and positively with 25OHD, alkaline phosphatase (ALP) and N-terminal propeptide of type-I procollagen (PINP).Summary: In practical terms, improving physical activity levels in individuals with SCI may help maintain or improve bone health. Monitoring specific biochemical markers may also offer insights in managing bone density. Further research is needed to understand how different factors interact with BMD in this population, which will help guide more targeted interventions.